The Kimberley, our place our future : conference report - Dixon, Rod.; Morris, Leon.; Kimberley Land Council (W.A.) (Derby, W.A. : Kimberley Land Council, 1998)
Report of conference in July 1998 (Broome) discussing issues related to the social and economic development of the Kimberley; papers on Indigenous themes annotated separately; includes workshop reports, map of Kimberley Aboriginal Communities and population numbers.
Keywords: Aboriginal Australians -- Western Australia -- Kimberley -- Economic conditions -- Congresses; Demography - Population dynamics; Economics - Economic development; Community development; Kimberley (W.A.) -- Economic conditions -- Congresses; Kimberley area (WA SD51, SD52, SE51, SE52)